Economic policy uncertainty and stock return momentum - Garima Goel; Saumya Ranjan Dash; Mário Nuno Mata; António Caleiro; Jo\~ao Xavier Rita; José António Filipe (Journal of Risk and Financial Management, 2021)
This paper investigates the relationship between economic policy uncertainty (EPU), an index capturing newspaper coverage of policy-related issues, and momentum profits. Momentum remains an unexplained anomaly. Our findings reveal a statistically negative association between EPU and hedge momentum portfolios. The short side portfolio dominates this effect as compared to the long side. EPU is statistically significant after controlling for macroeconomic variables. Furthermore, the paper conducts a battery of time series analysis, which highlights that EPU has a causal relationship with the hedge portfolio in the short run. On the other hand, the hedge portfolio has a long-term relationship with EPU, not the other way around.
Keywords: 330; economic policy uncertainty; macroeconomy; momentum